Comparison of Corticosteroids Effectiveness via High Volume Nasal Irrigation versus Conventional Nasal Spray after Endoscopic Sinus Surgery in Nasal Polyposi - Akram, Chaudhry Muhammad Bilal; Hakim, Abdul; Hussain, Aftab; Khan, Muhammad Zubair; Khan, Maryam; Butt, Kamran Ashfaq Ahmed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of two different methods of topical corticosteroid delivery techniques; conventional nasal spray versus high volume nasal irrigation with squeeze bottle, post-operatively in patients of nasal polyposis. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Ear Nose Throat, Combined Military Hospital, Kohat Pakistan, from Sep 2021 to Aug 2022. Methodology: A total of 80 patients diagnosed with nasal polyposis were recruited for this study. Selected patients were divided into two equal groups. Pre-operatively all patients were carefully assessed with the help of Sino-nasal outcome test 22 (SNOT 22) and Lund Kennedy Endoscopy score for severity of symptoms. Post-operatively, Group-A received Betamethasone via high volume irrigation by squeeze bottle whereas Group-B received the Beclomethasone via conventional nasal spray. This treatment plan continued for 3 months. Post-operatively, SNOT 22 and Lund Kennedy Endoscopy score assessment was carried out at 3 months. Results: Both groups were comparable with respect to demographic data. In Group-A pre-op median and interquartile range for SNOT score was 68 and 10 respectively and it was reduced to 14 and 5 post-operatively, whereas in Group-B, it was 68 and 10; 27 and 5.5 pre and post-operatively. Post-operative difference was significant (p-value=0.001). Similarly, in Group-A, pre and post-operative median and interquartile range for LKE score 6 and 1 respectively and 2 and 0, whereas in Group-B it was 6.22 and 0.4 and 1.5 with statistically significant post-operative difference (p-value=0.001). Conclusion: High volume irrigation with squeeze bottle is more effective method of delivering....